AXL is not essential for Zika virus infection in the mouse brain - Feng Li; Pei-Rong Wang; Lin-Bing Qu; Chang-Hua Yi; Fu-Chun Zhang; Xiao-Ping Tang; Li-Guo Zhang; Ling Chen (Emerging Microbes and Infections, 2017)
Emerging Microbes & Infections (2017) 6, e16; doi:10.1038/emi.2017.10; published online 29 March 2017